Labour force participation of rural youth in plantation sector of Northern Peninsular Malaysia - Norehan Abdullah,; Siti Aznor Ahmad,; Mohamad Amizi Ayob, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Malaysian agricultural industry is labour-intensive, especially in oil palm plantations. It is reported in 2013 that 69% of the total number of plantation worker in oil palm plantation are foreign and 31% are local. This proportion indicates the lack of interest of the local people to work in the industry which resulted in vast employment of foreign worker. It is believed that the cost of foreign worker recruitment has increased due to rising social and security problems caused by the foreign workers which incurred a hidden cost to palm oil production. This paper aims to investigate the factors of local young labour shortage in oil palm plantation sector in Perak, Perlis, and Kedah. Malaysia can reduce its dependency on foreign worker by identifying the occupational interest of rural youth in oil palm plantation. A survey questionnaire is used to collect data using random and purposive sampling method. A total number of 332 respondents from rural young labours staying in FELDA and FELCRA areas were analysed using Probit model. Results show the factors contributing to the probability to participate in oil palm plantation are age, wage, wage squared, gender, level of education, and mother’s occupation. Attraction factors that can possibly increase local youth participation in plantation sector includes improvement of working environment, job status, facility and benefit in plantation field.